The Impact Of State Budget Revenue On Economic Growth - Nguyen, Hoa Thi (The journal of contemporary issues in business and government, 2021)
The study of the impact of state budget revenue on economic growth has an important role in evaluating state budget revenue effectiveness. The article evaluates the state budget revenue and tests the impact of state budget revenues on Vietnam’s economic growth. With data collected for Vietnam from 1990 to 2019. The research variables are state budget revenue and Exchange rate, net domestic investment growth with the stationary test, and Autoregression distribution lag regression (ARDL). The ARDL model analysis results show that in the short-term, state budget revenue and exchange rate have a negative impact on the economic growth of Vietnam. In the long-term, state budget revenue and net domestic investment growth have a positive impact on economic growth, while the exchange rate does not affect economic growth. From these research results, the author also gives some policy implications based on state budget revenue, exchange rate, and net domestic investment growth to promote Vietnam’s economic development sustainably.